Testing the effectiveness of an acoustic deterrent for gray whales along the Oregon coast - Lagerquist, Barbara; Winsor, Martha; Mate, Bruce (Pacific Energy Ventures, LLC, 2012)
This study was conducted to determine whether a low-powered sound source could be effective at deterring gray whales from areas that may prove harmful to them. With increased interest in the development of marine renewal energy along the Oregon coast the concern that such development may pose a collision or entanglement risk for gray whales. A successful acoustic deterrent could act as a mitigation tool to prevent harm to whales from such risks. In this study, an acoustic device was moored on the seafloor in the pathway of migrating gray whales off Yaquina Head on the central Oregon coast. Shore-based observers tracked whales with a theodolite (surveyor’s tool) to accurately locate whales as they passed the headland. Individual locations of different whales/whale groups as well as tracklines of the same whale/whale groups were obtained and compared between times with the acoustic device was transmitting and when it was off. Observations were conducted on 51 d between January 1 and April 15, 2012. A total of 143 individual whale locations were collected for a total of 243 whales, as well as 57 tracklines for a total of 142 whales. Inclement weather and equipment problems resulted in very small sample sizes, especially during experimental periods, when the device was transmitting. Because of this, the results of this study were inconclusive. We feel that another season of field testing is warranted to successfully test the effectiveness of the deterrent, but recommend increasing the zone of influence to 3 km to ensure the collection of adequate sample sizes. Steps have been taken to acquire the necessary federal research permit modification to authorize the increased zone of influence and to modify the acoustic device for the increased power. With these changes we are confident we will be able to determine whether the deterrent is effective at deflecting gray whales. A successful deterrent device may serve as a valuable mitigation tool to protect gray whales, and other baleen whales, in the event that marine energy development poses a collision or entanglement risk.